Collaborative Strategies Between Government and SMEs In The Northern Coastal Region: Integrating Entrepreneurship Education To Support SDGS - Nashrullah, Ahmad Happy; Wati, Indah Kumoro; Sudarmiatin; Firmansyah, Rizky (PT. Maju Malaqbi Makkarana, 2024)
Global challenges such as economic inequality and environmental degradation have heightened the urgency of implementing sustainable business practices, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. In the North Coast region of East Java, MSMEs face unique challenges, including limited access to entrepreneurship education and insufficient government support. This study examines strategies for collaboration between the government and MSMEs, integrating entrepreneurship education to support sustainable development, aligned with SDG 8 and SDG 12. The novelty of this research lies in the integration of entrepreneurship education within public-private partnerships to enhance MSME sustainability while addressing local socio-economic issues. Using a qualitative research methodology, this study involves in-depth interviews, field observations, and document analysis to explore the experiences of MSME entrepreneurs, government officials, and educators in the region. The findings indicate that effective collaboration among stakeholders fosters innovation, strengthens MSME resilience, and promotes environmentally-friendly business practices. However, challenges remain in policy implementation and resource distribution. The implications of this research highlight the importance of institutionalizing entrepreneurship education within government programs and strengthening public-private collaboration. These steps can serve as a model for other regions to simultaneously drive economic growth and sustainability, contributing to the achievement of the SDGs by 2030